1991
DOI: 10.2172/5534951
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary screening of contaminants in the off-site surface water environment downstream of the US Department of Energy Oak Ridge Reservation

Abstract: The draft version of this report was distributed in March 1990. Only minor changes were made for this final version; substantial revisions to the draft were unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 2 publications
1
25
0
Order By: Relevance
“…The focus is on contaminants of potential concern (COPCs) that were identified in previous human health risk screening reports ("able 5.1). In their screening assessment, Hoffman et al (1991) identified PCBs in fish and external exposure to radiation from lnCs in dredged sediments as exposure pathways and contaminants that are of potential concern. Cook et al (1992) confirmed the exposure pathways and COPCs based on CRRI Phase 1 data.…”
Section: Human Health Rise Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The focus is on contaminants of potential concern (COPCs) that were identified in previous human health risk screening reports ("able 5.1). In their screening assessment, Hoffman et al (1991) identified PCBs in fish and external exposure to radiation from lnCs in dredged sediments as exposure pathways and contaminants that are of potential concern. Cook et al (1992) confirmed the exposure pathways and COPCs based on CRRI Phase 1 data.…”
Section: Human Health Rise Assessmentmentioning
confidence: 99%
“…Previous risk evaluations have not identified any high-priority contaminants in LWBR surface water (Cowser and Snyder 1966, Hoffman et al 1991, Cook et al 1992.…”
Section: Water Datamentioning
confidence: 99%
See 3 more Smart Citations